Image of the Defender of Faith and Fatherland in the Tales of the Azov Cycle - M. V. Melikhov (Научный диалог, 2019)
The traditional and original features of the plot structure and the system of images of the cycle of stories about the conquest of the Turkish fortress of Azov by the Zaporozhye Cossacks in 1637 and about their "sitting" under siege in 1641 are investigated. An analysis of the texts showed that they are characterized by an even greater addiction to digital data on the number of enemy troops and to detailed technical information about their weapons than for military texts of Old Russian literature. Observations of the texts showed that the battle scenes, key for the military story, and, first of all, the fights, are much less introduced in the narratives, and they practically do not mention battles using cold arms traditional for the military narrative. The differences in the system of images of the Azov stories (Cossacks and their enemies) from the old Russian military stories in the characteristics of events, details of military life and battle scenes are considered. It was established that the authors of the Azov novels set as their goal the creation of a biased fictionalized narrative in which real facts were freely interpreted, combined with folklore motifs, with a few lexical and situational formulas of military narratives and fictional episodes.